Increased Rates of Vitamin D Insufficiency in Boys With Duchenne Muscular Dystrophy Despite Higher Vitamin D3 Supplementation. (March 2019) - Bian, Qian; McAdam, Laura; Grynpas, Marc; Mitchell, Jane; Harrington, Jennifer
Vitamin D supplementation is important for many chronic pediatric conditions to help maintain bone health; however, there is little evidence about how disease-related factors affect vitamin D status. The objective was to compare 25-hydroxyvitamin D (25(OH)D) concentrations in 3 pediatric cohorts (Duchenne muscular dystrophy [DMD], systemic lupus erythematosus [SLE], and osteogenesis imperfecta [OI]). In a retrospective study of 367 subjects, children with DMD had increased prevalence of vitamin D insufficiency (25% vs 14% [SLE] and 10% [OI], P = .002), despite higher vitamin D3 supplementation doses. Boys with DMD also had higher weight, fat mass, and lower lean mass percentage Z scores. DMD was associated with having higher rates of vitamin D insufficiency than other comparable pediatric chronic disease cohorts, the effect of which may be modulated by clinical factors such as increased adiposity. While corroboration of these results is needed given baseline differences between the patient groups, greater vitamin D supplementation doses may be required to achieve optimal serum 25(OH)D concentrations in boys with DMD.